INVESTIGATING THE EFFECT OF 1% CURCUMIN GEL AND PLACEBO ON PATIENTS WITH PLAQUE PSORIASIS: Life Sciences-Pathology - REZA YAGHOOBI; MEHRNAZ SOGHRATI; NADER PAZYAR; NAJMEH PARVIN (International Journal of Life Science and Pharma Research, 2022)
Psoriasis is a common, chronic, and immunogenetic disease resulting from proliferation of keratinocytes that exists in five forms of plaque, guttate, inverse, pustular, and erythrodermic. Itchy skin is one of the most common symptoms of the disease and influences life quality. This study aimed to compare the effect of 1% curcumin gel made by the Center for Pharmaceutical Technologies Development of Jundishapur University in mild to moderate plaque psoriasis in a randomized and double-blind study as an inexpensive biologically active drug with placebo. The methods of data analysis used in this study - include descriptive statistics, mean, standard deviation, minimum and maximum pasi-score, dermatology life quality index (DLQI), and itchy skin index (QOL-Itchy) as well as inferential statistics including paired t-test, chi-square, and Mann-Whithney test. The analysis was performed by statistics consultant. In the intervention group, the average pasiscore before the treatment was 3.1; two weeks after the treatment it was 1.91 and the pasi-score decrease was significant. Also the average pasi-score reduction in this group was 30.46%; 19% of the patients showed weak therapeutic response, 56% showed average therapeutic response, 13% showed good therapeutic response, and 12% showed excellent therapeutic response. In the control group, the average pasi-score before the treatment was 3.17; after the treatment it was 2.75 where no significant difference was observed. The average pasi-score reduction in this group was 20.4% in which 84% of the patients showed weak response, 8% showed average response, and 8% showed excellent response. A comparison was performed between pasi-scores in intervention and control groups before and after the treatment by employing statistical tests. Though no significant difference was observed, the efficiency size showed that prescription of medicine has a modest effect on patients. In the intervention group, the second week after the end of treatment, the average pasi-score was 1.19; its effect was significant compared with the score before the treatment. The average pasi-score in the control group was 2.75; no significant difference was observed compared with the average score before the treatment. These results showed the continuous effect of medicine after the discontinuation of treatment and no recurrence during this period was observed. The results of this study and previous studies show that curcumin can have an important role in the treatment of psoriasis. It is important because curcumin is an inexpensive drug with less side effects than the existing drugs.